Professor Hicks' Index Number Theorem - Marris, R. L. (Review of Economic Studies, 1957)
Journal Article Professor Hicks' Index Number Theorem Get access R. L. Marris R. L. Marris Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 25, Issue 1, October 1957, Pages 25–40, https://doi.org/10.2307/2296119 Published: 01 October 1957